SPILLOVER EFFECTS OF THE SUB-PRIME MORTGAGE CRISIS TO THE ASIAN STOCK MARKETS - Esta Lestari (Economic Journal of Emerging Markets, 2012)
AbstractThis paper aims to analyze the effects of the sub-prime mortgage crisis on several Asian stock markets. An Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) model is employed to provide an empirical evidence of the direct spillover. The indirect effect is measured through the spillover effects from the increased volatility in the U.S. stock markets to the Asian stock markets. The results showed that the market integration occurs within Asian stock markets. Meanwhile the asymmetric effects are evident for all the Asian countries stock markets, indicating that financial markets in Asia are suffered more from negative news (shocks) lead to more volatilities compared to positive news. Keywords: Stock market, sub-prime mortgage crisis, volatility, spillover effectJEL classification numbers: C22, F36, G15AbstrakPaper ini bertujuan untuk menganalisis pengaruh krisis sub-prime mortgage pada beberapa pasar saham Asia. Model Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) digunakan untuk mendapatkan bukti empiris dari kenaikan volatilitas dalam pasar saham Amerika pada pasar-pasar saham Asia. Hasil analisis memperlihatkan bahwa integrasi pasar terjadi di dalam pasar saham Asia. Sementara itu, pengaruh asimetris terbukti terjadi di pasar-pasar saham Asia, mengindikasikan bahwa pasar-pasar keuangan di Asia menderita lebih parah sebagai akibat dari kejutan negatif dibandingkan dengan dampak dari kejutan positif.Kata kunci: Pasar saham, krisis sub-prime mortgage, volatilitas, pengaruh spillover JEL classification numbers: C22, F36, G15